School through the eyes of children... are we just bricks in the wall? - Oliveira, A.; Moura, L.; Dias, R. (Mediterranean Journal of Social Sciences, 2015)
Over the years it has been debated what should be the role of school, which is the best teaching practices, and the most appropriate methods in primary education. However, rarely we are available to hear who is at the center of any education system... The student, the child within… We may wonder what children really think. What are their needs and aspirations? Listening to children, we can better understand their ideas, feelings, desires and dreams, about teaching and the school they attend, and how this is reflected in their behavior and development. Their representations of school allow us to rethink education and school itself. So, in this study, we were guided by the eyes of children aged between 8 and 11 years, of both sexes, attending elementary school, in Lisbon. What do they think and how they feel about school? What are their wishes and how they imagine school should be? These were the main objectives. The data was gathered using free associations of words, from questions individually made, and examined through Factorial Correspondence Analysis. Children link school both to playful and learning dimensions. In fact the most important for all of them is the playful side of school, a place where they can meet peers and establish important relations, also with teachers. They care about each other, they wish to learn and feel free. They yearn for a better school… Remembering Pink Floyd, we hope we are not just contributing for more 'bricks in the wall'.